PENGARUH MODEL PBL DENGAN INTEGRASI TRI HITA KARANA MENINGKATKAN KETERAMPILAN KOLABORATIF PADA PEMBELAJARAN IPS SD - Sepnita Lestari Yanti, Ni Putu; I Wayan Lasmawan; I Wayan Kertih; Ida Bagus Putu Arnyana; I Wayan Suja (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the effect of the PBL model with Tri Hita Karana integration in improving collaborative skills in elementary school students' social studies learning. This research method is an experimental study with a quasi-experimental research type, data collection methods with collaborative skills questionnaires. The population of the study were all sixth grade students of the Kelusa cluster. The research sample was taken by simple random sampling, namely SD N 1 Kelusa experimental group and SDN 2 Kelusa control group. The results of the study obtained an average of 81.5, a mean value of 81, and a mode of 78. While the control class data averaged 59, a middle value of 59, and a mode of 50 and the results of the t-test obtained a significance value of 0.001 which means that there is an effect of the PBL model with Tri Hita Karana integration (THK) on the collaborative skills of elementary school students in social studies learning. The conclusion is that there is a significant effect of the PBL model with integrated Balinese local wisdom Tri Hita Karana on collaborative skills in elementary school social studies learning. Suggestions for further research include conducting research using the PBL model to measure other aspects of skills in accordance with the demands of the 21st century, such as communication skills, critical thinking, and inserting local wisdom from the surrounding area as a form of cultural responsiveness.